Pengaruh Gaya Kepemimpinan dan Kesejahteraan Terhadap Kinerja Karyawan (Studi Kasus pada Hotel Selabintana) - Purwanto Rahardjo; Ce Gunawan; Isriyani Isriyani (Institut Manajemen Wiyata Indonesia & Asosiasi Peneliti Manajemen Indonesia, 2021)
This study aims to determine: (1) the influence of leadership style on employee performance, (2) the influence of welfare on employee performance, and (3) the influence of leadership style and welfare on employee performance. The subjects of this research are employees who work at Selabintana Hotel. The number of respondents in this study were 102 employees. The method of collecting data through a survey using a questionnaire. The analysis technique used in this research is multiple linear regression analysis. The results showed that (1) leadership style had a positive and significant effect on employee performance, so Ha1 is accepted; (2) welfare has a positive and significant effect on employee performance, so Ha2 is accepted; (3) simultaneously, leadership style and welfare have a positive and significant effect on employee performance with detemination coefficient of 0,409 so that Ha3 is accepted.